2004
DOI: 10.1002/ange.200400650
|View full text |Cite
|
Sign up to set email alerts
|

Im Goldenen Zeitalter der Organokatalyse

Abstract: Unter dem Begriff “Organokatalyse” werden chemische Reaktionen zusammengefasst, die durch Zusatz substöchiometrischer Mengen von organischen Verbindungen beschleunigt werden. Das Interesse an diesem Forschungsgebiet und den damit verbundenen neuen Konzepten hat in den vergangenen Jahren stark zugenommen. Viele der bekannten organokatalytischen Reaktionen sind bezüglich ihrer Effizienz und Selektivität mit etablierten organischen Reaktionen vergleichbar, und die Organokatalyse hat sich beim Aufbau komplexer Mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
97
0
9

Year Published

2005
2005
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 724 publications
(106 citation statements)
references
References 470 publications
0
97
0
9
Order By: Relevance
“…[15] Nevertheless, in an effort to develop more applicable asymmetric transformations of cyanoacetates, we found that the Michael acceptors were not limited to vinyl sulfones. Here we would like to report the highly enantioselective Michael addition of a-substituted cyanoacetates to vinyl ketones promoted by simple bifunctional thiourea/tertiary amine organocatalysts, [16] giving a more efficient protocol for structurally variable acyclic and cyclic b 2,2 -amino acid esters.…”
Section: Introductionmentioning
confidence: 99%
“…[15] Nevertheless, in an effort to develop more applicable asymmetric transformations of cyanoacetates, we found that the Michael acceptors were not limited to vinyl sulfones. Here we would like to report the highly enantioselective Michael addition of a-substituted cyanoacetates to vinyl ketones promoted by simple bifunctional thiourea/tertiary amine organocatalysts, [16] giving a more efficient protocol for structurally variable acyclic and cyclic b 2,2 -amino acid esters.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] The immobilization of organocatalysts is important for the large-scale production of chiral compounds, which are abundant as biologically active molecules and drugs. The key challenges for heterogeneous organocatalysts are to develop cost-effective strategies for immobilization and to use easily recoverable supports which can help to overcome the problems of mechanical loss of the support during recycling experiments.…”
mentioning
confidence: 99%
“…[1] Since the 1,4-F-C reaction of a,b-unsaturated carbonyl compounds with pyrrole derivatives catalyzed by small organic molecules, so-called organocatalysts, [2] was accomplished by MacMillan and co-workers, [3a] the development of organocatalytic F-C reactions has been a challenging topic of continued interest in synthetic organic chemistry. To date several efficient organocatalysts have been reported.…”
mentioning
confidence: 99%